Endoscopic mucosal resection and endoscopic submucosal dissection for en bloc resection of superficial pharyngeal carcinomas - Okada, K.; Tsuchida, T.; Ishiyama, A.; Taniguchi, T.; Suzuki, S.; Horiuchi, Y.; Matsuo, Y.; Yoshizawa, N.; Suganuma, T.; Omae, M.; Kubota, M.; Hirasawa, T.; Yamamoto, Y.; Inamori, M.; Yamamoto, N.; Nakajima, A.; Fujisaki, J.; Hoshino, E.; Kawabata, K.; Igarashi, M. (Endoscopy, 2012)
Background and study aim: Endoscopic mucosal resection (EMR) and endoscopic submucosal dissection (ESD) are being used increasingly to treat superficial oropharyngeal and hypopharyngeal carcinomas. The aim of this study was to clarify whether ESD provided better results than EMR for en bloc and complete resection of superficial pharyngeal carcinomas.Patients and methods: A total of 76 superficial pharyngeal carcinomas in 59 consecutively treated patients were included. Patients underwent either conventional EMR (using a transparent cap or strip biopsy) (n = 45 lesions) or ESD (n = 31 lesions) between October 2006 and January 2011. The rates of en bloc resection, complete resection (defined as en bloc resection with tumor-free margins), major complications, and local recurrence were evaluated retrospectively as the therapeutic outcomes.Results: ESD yielded significantly higher rates of both en bloc and complete resection compared with EMR (en bloc 77.4 % [24/31] vs. 37.8 % [17/45], P = 0.0002; complete 54.8 % [17/31] vs. 28.9 % [13/45], P = 0.0379). ESD was more frequently complicated by severe laryngeal edema (4/21 [19.0 %] vs. 1/31 [3.2 %], P = 0.1446) and was also more time-consuming (124.9 ± 65.1 minutes vs. 57.2 ± 69.6 minutes; P = 0.0014). Local recurrence was observed more often after EMR than after ESD (3/45 [6.7 %] vs. 0/31 [0 %]), although this difference did not reach statistical significance (P = 0.2658).Conclusions: ESD appears to be a superior method of endoscopic resection of superficial pharyngeal carcinomas for achieving both en bloc and complete resection, although these benefits were also associated with a higher incidence of complications and a significantly longer procedure time. Large prospective studies are needed to compare ESD with conventional EMR for superficial pharyngeal carcinomas.